Agreement in the agreement for the rejuvenation of flats between the National Housing Public Company (Perum Perumnas) and residents in Sukaramai flats - Alifa Nadra (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This study discusses how the rights and obligations between Perum Perumnas and residents towards the rejuvenation process of Sukaramai Flats, how Perum Perumnas is responsible for the rejuvenation process of Sukaramai Flats and how the role of the Association of Residents of Flats Units (PPRS) in maintaining the balance of rights and obligations between residents and Perum Perumnas related to the rejuvenation process of Sukaramai Flats. This type of research uses normative juridical research that is descriptive analysis. The data used to answer the problems in this study are secondary data and primary data derived from literature and field research. The results of this study provide conclusions, rights and obligations between Perum Perumnas and residents, namely residents get equivalent replacement residential units, the obligation of residents to submit a letter of approval regarding the willingness to replace units to Perum Perumnas. Perum Perumnas' rights to improve the quality of flats and Perum Perumnas' obligation to ensure that residents get equivalent replacement residential units. Perum Perumas' responsibility for the process of rejuvenating flats is to provide temporary occupancy costs, issue title certificates for new flats, and provide public facilities to residents. The role of PPRS in maintaining the balance of rights and obligations of the parties is to sign a letter of approval for the rejuvenation of the Sukaramai Flats. The advice that can be given from the results of this study is to reorganize the rights and obligations of the parties after the rejuvenation process of the Sukaramai Flats so that there is a continuity of rights and obligations during the rejuvenation process of the Sukaramai Flats and Perum Perumnas adds to the form of accountability and the role of PPRS is further enhanced to help residents both during the rejuvenation process of the Sukaramai Flats and after the rejuvenation process of the Sukaramai Flats.